IMPACT OF TECHNOLOGY ADOPTION ON RURAL DEVELOPMENT (International Journal of Food and Nutritional Sciences, 2023)
In India technology act vital role so this study portrays its impact and adoption on rural development especially in villages. The use of agricultural technologies determines how the increase in educational technology output impacts on poverty levels and environmental degradation. Experience and evidence from countries within and around the Indian region indicate that returns to adoption of technology and its development could be very high and far reaching. The factors affecting technology adoption are assets, income, institutions, vulnerability, awareness, labor, and innovativeness by rural educate people. Technologies is requiring few assets, have a lower risk premium, and is less expensive have a higher chance of being adopted by rural educated people. Some of these technologies are more efficient in their use of scarce production resources than modern technologies. Modern researchers should therefore seek to understand the rationale behind traditional behavior in technology use.